ON THE ISSUE OF THE EFFECTIVENESS OF THE MAIN METHODS OF TEACHING FOREIGN LANGUAGES (British Journal of Global Ecology and Sustainable Development, 2024)
The article presents a comprehensive review of the basic teaching methods. The advantages and limitations of each method are analyzed, as well as the problems faced by researchers and practitioners in their application. The purpose of the article is to provide the reader with a comprehensive understanding of existing teaching methods, their features and scope, as well as to help in choosing the most appropriate approach to solving specific tasks in the field of teaching a foreign language.